2020
DOI: 10.2147/cmar.s244317
|View full text |Cite
|
Sign up to set email alerts
|

<p>hsa_circ_0008285 Facilitates the Progression of Cervical Cancer by Targeting miR-211-5p/SOX4 Axis</p>

Abstract: Introduction: Emerging evidence has demonstrated that circRNAs are implicated in the progression of cervical cancer (CC). However, the roles and underlying mechanisms of circRNAs remain unclear in CC. Methods: QRT-PCR was performed to detect hsa_circ_0008285 expression in CC tissues and cell lines. The roles of hsa_circ_0008285 on CC progression were explored by function assays. Next, the underlying mechanisms of hsa_circ_0008285 in CC progression were determined by bioinformatics analysis, dual-luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…And miR-138-5p can inhibit the malignant progression of prostate cancer [ 38 ] and lung cancer growth, through the miR-138-5p/FOXC1 pathway [ 39 ]. miR-211-5p has been confirmed to be related to a variety of cancers, such as cervical cancer [ 40 ], the nonsmall cell lung cancer cell [ 41 ], breast cancer [ 42 ], oral squamous cell carcinoma [ 43 ], and papillary thyroid cancer [ 44 ]. miR-642a-5p and miR-5000-3p were found have important effects on colon cancer [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…And miR-138-5p can inhibit the malignant progression of prostate cancer [ 38 ] and lung cancer growth, through the miR-138-5p/FOXC1 pathway [ 39 ]. miR-211-5p has been confirmed to be related to a variety of cancers, such as cervical cancer [ 40 ], the nonsmall cell lung cancer cell [ 41 ], breast cancer [ 42 ], oral squamous cell carcinoma [ 43 ], and papillary thyroid cancer [ 44 ]. miR-642a-5p and miR-5000-3p were found have important effects on colon cancer [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…circ_0008285 may participate in the development of GDM by affecting cell metabolisms and cell cycles during pregnancy. Past studies have indicated that has_circ_0008285 can competitively bind to miR-211-5p as a miRNA sponge, release SOX4, and promote the self-renewal and proliferation of cervical cancer cells [ 18 ]. It is known that the proliferation of trophoblast cells is increased during hyperglycemia and that maternal diabetic women have higher placenta weight [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNA is an endogenous ncRNA that has attracted widespread attention owing to its unique loop structure, high stability, and conservation across evolution [ 25 ]. Accumulating data suggests that the dysregulated levels of circRNAs seen in AML exerted a crucial function in cancer progression and development.…”
Section: Discussionmentioning
confidence: 99%